SIKAP PETANI TERHADAP PROGRAM GELAR LAPANG INOVASI PERTANIAN (GLIP) BERBASIS PADI DI KECAMATAN GULUK-GULUK, KABUPATEN SUMENEP - Sonia Aprilia Susanta; Agung Wibowo; Emi Widiyanti (AGRITEXTS: Journal of Agricultural Extension, 2019)
This research was aimed to investigate the attitudes of farmers toward Agricultural Innovation Field Organizing Program Based on Paddy, to study farmer’s attitude toward program, to study the factors that form the attitude of farmers toward the program, and analyzing the relationship between factors influencing farmer’s attitude toward program. The basic method was quantitative research with survey technique. Location of research was determined purposivelywhere is District Guluk-Guluk Sumenep Regency. The sample was determined by random sampling technique, who are 43 rice farmers participated in the Agricultural Innovation Field Organizing Program Based on Paddy for the August-November period. In determining respondent’s number from each farmer group, it used proportional random sampling. The data used that for analysiswere primary data and secondary data. Data was analyzed by Rank Spearman correlation coefficient (rs)to know the relation of factors that formed attitude with farmer’s attitude toward Agricultural Innovation Field Organizing Program Based on Paddy. The factors that formed the farmers’ attitude in Guluk-Guluk Sub-district of Sumenep Regency were personal experience in very high category, non-formal education in very high category, cultural role in high category, the role of others that are considered important in medium category, media exposure in low category, and extension roles in very high categories.Based on rank spearman (rs), showed thatthere was a significant relationship between personal experience, non-formal education, the role of culture, and the role of investigator with farmer’s attitudes toward the program, while the roles of others that were considered important and mass media exposure had no significant relationship with farmers' attitudes toward the program